The Impact of Digital Content and Information Quality through Instagram @speakingid on Public Speaking Training Interest in Indonesia - Hapsari, Ramita; Jayanti, Karina; Agitashera, Dwi (Journal of Content and Engagement, 2026)
This study examines the Impact of digital content and information quality on public speaking training interest among followers of Instagram @speakingid in Indonesia. Using a quantitative explanatory survey design, data were collected from N = 300 respondents through an online questionnaire with a four-point Likert scale. Multiple linear regression analysis was conducted using SPSS. The results show that digital content and information quality have a statistically significant effect on training interest, both partially and simultaneously. Information quality has a greater standardized coefficient compared to digital content. The coefficient of determination (R² = 0.533) indicates that 53.3% of the variance in training interest is explained by the two independent variables. These findings extend Uses and Effect Theory by empirically demonstrating how specific content attributes and perceived information quality within Instagram-based educational accounts relate to interest in skill development. Unlike prior studies that primarily focus on engagement or purchase intention, this study specifically examines training interest in the context of informal public speaking education in Indonesia.